Differential expression of members of the IGF system in OPU-derived oocytes from Nelore (Bos indicus) and Holstein (Bos taurus) cows - Satrapa, Rafael A.; Castilho, Anthony S.; Razza, Eduardo M.; Pegorer, Marcelo F.; Puelker, Raquel; Barros, Ciro M. (Elsevier, 2013)
The insulin-like growth factor (IGF) system is related to quality of oocytes and embryos. The aim of this study was to investigate the mRNA levels of IGF1 and IGF2 and their receptors, IGFR1 and IGFR2, as well as IGFBP2, IGFBP4, and PAPP-A in oocytes from Nelore compared to Holstein cows. Pools of oocytes (20 oocytes/pool) from Nelore (n=8 pools) and Holstein (n=4 pools) were obtained via ovum pick-up (OPU, 10 sessions) and cumulus cells and zona pellucida were removed. The pools were submitted to total RNA extraction. Expression of members of the IGF system was assessed by real time RT-PCR. The mRNA expression of IGF1 and IGF2, IGFR1 and IGFR2, IGFBP2 and IGFBP4 was significantly higher (P<0.01) in oocytes from Holstein whereas the expression of PAPP-A was significantly higher (P<0.05) in oocytes from Nelore cows. The high PAPP-A expression and the low expression of IGFBP2 and IGFBP4 are associated with more efficient degradation of IGFBPs, which results in greater bioavailability of IGF in Nelore oocytes when compared to the Holstein. © 2013 Elsevier B.V.
Keywords: Bovine; IGF; IGFR; Oocyte; OPU; PAPP-A; Bos indicus; Bos taurus; Bovinae